1995
DOI: 10.1046/j.1365-313x.1995.08050763.x
|View full text |Cite
|
Sign up to set email alerts
|

The CIC library: a large insert YAC library for genome mapping in Arabidopsis thaliana

Abstract: A new Arabidopsis thaliana (ecotype Columbia) genomic library has been constructed in Yeast Artificial Chromosomes: the CIC library (for CEPH, INRA and CNRS). Optimization of plant culture conditions and protoplast preparation allowed the recovery of large amounts of viable protoplasts. Mechanical shearing of DNA was minimized by isolation of DNA from protoplasts embedded in agarose. Cloning of large inserts was favored by including two successive size fractionation steps (after partial EcoRI digestion and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 0 publications
3
125
0
2
Order By: Relevance
“…CSD1 was identified on TAMUBAC10I10, 20M22, and 30M24. These BACs are coincident with the CICYAC8C10, placing CSD1 at the top of chromosome 1 between markers PAI1 and PHYA (http://cbil.humgen.upenn.edu/ϳatgc/physicalmapping; Creusot et al, 1995). This location agrees with the position identified for the genomic sequence for CSD1 in the Arabidopsis genome project (http://genome-www3.…”
Section: Map Positions Of the Known Sod Structural Genessupporting
confidence: 78%
See 1 more Smart Citation
“…CSD1 was identified on TAMUBAC10I10, 20M22, and 30M24. These BACs are coincident with the CICYAC8C10, placing CSD1 at the top of chromosome 1 between markers PAI1 and PHYA (http://cbil.humgen.upenn.edu/ϳatgc/physicalmapping; Creusot et al, 1995). This location agrees with the position identified for the genomic sequence for CSD1 in the Arabidopsis genome project (http://genome-www3.…”
Section: Map Positions Of the Known Sod Structural Genessupporting
confidence: 78%
“…To map CSD3 and the other SOD loci, PCR primers were designed that specifically amplified the SOD genes from pooled CICYAC clones in a multiplex collection of CICYAC DNA (Creusot et al, 1995). These oligonucleotides are listed in Table I.…”
Section: Map Positions Of the Known Sod Structural Genesmentioning
confidence: 99%
“…5S rDNA units were amplified by PCR using CIC YACs as template DNA (Creusot et al 1995). The primer sequences, the positions of which are given in Figure 2B, were: dG3: GNCAAANTTNGCATGTG and dG4: CNGTNTANAAGT TATNGAGTC.…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…We verified the map position of the Ds(Hyg) causing the im-2 mutation. We found that the Ds(Hyg) flanking sequence hybridizes with yeast artificial chromosomes (YACs) CIC5A4, CIC5C2, and CIC7A5 from the CIC library (Creusot et al, 1995). These YACs were mapped previously to the position of markers JBG9 on the chromosome 4 physical map (Lister and Dean, 1993;Schmidt et al, 1995) within the same area at which im has been mapped.…”
Section: Ds(hyg) Is Associated With Im-2mentioning
confidence: 99%